Metal atom (Zn, Cd and Mg) luminescence in solid neon - Healy, Brendan; Kerins, Paul; McCaffrey, John G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Luminescence spectroscopy of the metal atoms Mg, Zn and Cd isolated in solid neon is recorded using pulsed synchrotron radiation excitation of the ns1np1 1P1–ns2 1S0 resonance (n = 3, 4 and 5 respectively) transitions. Two features, a dominant band and a red-shoulder, are identified in the UV absorption spectra of Zn/Ne and Cd/Ne. Excitation of these features yields distinct emission bands with the red-shoulder absorption producing the smaller, Stokes-shifted emission. Nanosecond decaytime measurements, made with the time correlated single photon counting technique indicate the emission bands arise from the spin singlet 1P1 → 1S0 transition. Hence, it is concluded the duplication of absorption and emission features in the Cd/Ne and Zn/Ne systems arises from metal atom occupancy in two distinct sites. In contrast, Mg/Ne luminescence consists of single excitation and emission bands, indicative of occupancy in just one site. The occurrence of distinct photophysical characteristics of the linewidths, Stokes shift and lifetimes in the Mg/Ne system, compared with those recorded for Zn/Ne and Cd/Ne, is rationalised in terms of a different site occupancy for atomic Mg. Accurate interaction potentials for the ground states of the M·Ne diatomics are used to analyse site occupancies and interpret this contrasting behavior.